Analisis Penetapan Itsbat Nikah Terhadap Pasangan Perkawinan Siri Dan Kepastian Hukum Pada Anak - Sulistyorini Pevey Yuliana; Anjar Sri Ciptorukmi Nugraheni (LPPM Universitas Sains dan Teknologi Komputer, 2024)
This research intends to describe and examine the issue of the appropriateness of the judge's consideration in determining the marriage Isbat for unregistered marriage couples and legal certainty for children after and before the determination of the marriage Isbat which is linked to Positive Law in Indonesia. The types of data used in this research are primary and secondary data, which includes primary, secondary and tertiary legal materials. Data was collected through literature research and field studies, and the research method applied was a qualitative method and the results were presented descriptively. The results of the resulting observations show that the appropriateness of the judge's considerations in determining the marriage isbat for unregistered marriage couples to Indonesian positive law at the Boyolali Religious Court is in accordance with positive legal regulations in Indonesia including the Compilation of Islamic Law and Law Number 1 of 1974. guarantee of legal certainty to married couples regarding the validity of their marriage as well as ensuring that the status and rights of children are fulfilled. After a decision is made by the judge, the legal certainty of the husband and wife and the status of their children becomes valid in the eyes of Indonesian law and the decision from the Religious Court can be utilized. as it should be.